Integrating evidence in disability evaluation by social insurance physicians - Kok, Robin; Hoving, Jan L.; Verbeek, Jos; Schaafsma, Frederieke G.; van Dijk, Frank JH (Scandinavian Journal of Work, Environment & Health, 2011)
' ' OBJECTIVE ': 'The aim of this study was to explore applying the method of evidence-based medicine (EBM) to resolve common questions in the field of disability evaluation. ' ' METHODS ': 'We used three clinical questions corresponding to problems encountered by insurance physicians in daily practice to explore opportunities for and barriers to the application of EBM. The questions fell under two topics: the prognosis of work ability and the effectiveness of interventions to enhance work participation. We used the four-step EBM strategy: (i) formulation of a clinical question, (ii) searching the literature, (iii) appraisal of the evidence, and (iv) implementation of the findings into clinical practice. We restricted the searches to PubMed (Medline). ' ' RESULTS ': 'For rheumatoid arthritis, we found evidence on the prognosis of work disability over a long-term period. For remaining sciatica after lumbar discectomy, we found evidence for the stability of the limitations at this stage. For depression with co-morbid alcoholism, we found evidence that treatment of both conditions would enhance work participation. The searches were effective and efficient. The interpretation of the findings was hampered by a lack of consensus in the literature about outcomes such as the concept of a poor prognosis of work ability. ' ' CONCLUSIONS ': 'The EBM strategy and methods can be used by social insurance physicians to find and apply evidence for common questions in disability evaluation. The World Health Organization’s International Classification of Functioning, Disability, and Health (ICF) model is instrumental in this, although more consensus on central outcome measures is needed. Further research is needed on the translation of evidence into practice. Development of valid specific search strategies for physicians in disability evaluation would improve the implementation of EBM.
Keywords: disability evaluation; EBM; evidence; evidence-based medicine; ICF; insurance medicine; insurance physician; occupational health; social insurance; work capacity; work disability; work participation